Mathematical Models of Bead-Spring Jets during Electrospinning for Fabrication of Nanofibers - DASRI, Thananchai (Walailak Journal of Science and Technology (WJST), 2012)
Electrospinning is a popular technique to produce structures in the form of nanofibers. These nanofibers can be used for many applications such as filtration composites, insulator and energy storage. The technique is based on the electrostatic force that acts on the polymeric solution. However, during the electrospinning process the liquid jet shows unstable behavior. This problem causes the random formation of nanofibers. This article focuses on the mathematical models to describe the dynamics behavior of the fluid jet in the electrospinning process. There are a lot of different parameters in the model. Variation in these parameters results in a change in jet behaviors. This brief review is a summary of the authors’ recent work. The Reneker’s model and Wu’s model are used to describe the dynamics behavior of the jet used in electrospinning.